PENERAPAN SISTEM KEUANGAN DESA (SISKEUDES) DALAM MEWUJUDKAN AKUNTABILITAS PEMERINTAHAN DESA - Dinda Novyasari Maharani; Fajar Syaiful Akbar (BAJ: Behavioral Accounting Journal, 2020)
Village development and growth is currently experiencing rapid progress, this is indicated by the large amount of village funds and other sources of village income. Therefore, the government applies Law No. 6 of 2014 concerning Villages as the Village Law in Indonesia. This law requires the village government to hold the community accountable for the state funds that have been used. To realize this responsibility, the central government represented by BPKP developed the application of the village financial system or called SISKEUDES as a village tool in realizing its accountability. The research method used is a qualitative approach. Data obtained by interviews and direct observation techniques in the Village Hall Banjaragung. The results of this study indicate that the existence of SISKEUDES in Banjaragung Village helps the village accountability process to the local government and the community with the existence of village financial reports produced by this application. Banjaragung Village has implemented SISKEUDES which is adjusted to Permendagri No. 20 of 2018 concerning Village Financial Accounting, thus the quality of reporting can be accounted for based on the prevailing village accounting.